Radiofrequency and 2.45 GHz electron cyclotron resonance H− volume production ion sources - O Tarvainen; S X Peng (New Journal of Physics, 2016)
The volume production of negative hydrogen ions ( ${{\rm{H}}}^{-}$ ) in plasma ion sources is based on dissociative electron attachment (DEA) to rovibrationally excited hydrogen molecules (H _2 ), which is a two-step process requiring both, hot electrons for ionization, and vibrational excitation of the H _2 and cold electrons for the ${{\rm{H}}}^{-}$ formation through DEA. Traditionally ${{\rm{H}}}^{-}$ ion sources relying on the volume production have been tandem-type arc discharge sources equipped with biased filament cathodes sustaining the plasma by thermionic electron emission and with a magnetic filter separating the main discharge from the ${{\rm{H}}}^{-}$ formation volume. The main motivation to develop ion sources based on radiofrequency (RF) or electron cyclotron resonance (ECR) plasma discharges is to eliminate the apparent limitation of the cathode lifetime. In this paper we summarize the principles of ${{\rm{H}}}^{-}$ volume production dictating the ion source design and highlight the differences between the arc discharge and RF/ECR ion sources from both, physics and technology point-of-view. Furthermore, we introduce the state-of-the-art RF and ECR ${{\rm{H}}}^{-}$ volume production ion sources and review the challenges and future prospects of these yet developing technologies.